Physiological Characteristics of Junior Taekwondo Athletes of Student Training Education Centres in Java - Tommy Apriantono; Muhamad Fahmi Hasan; Indria Herman; Didi Sunadi; Bagus Winata; Agung Dwi Juniarsyah (Universitas Pendidikan Indonesia, 2020)
The measurement of physiological characteristics of junior athletes is important to do as the first step in determining and designing training designs that are appropriate for athletes. The purpose of this study was to measure the physiological characteristics of Indonesian Junior Taekwondo athletes, who were members of student training education centres (PPLP), in West Java, Central Java, and East Java provinces. This qualitative descriptive study conducted the process of collecting data of 8 male Taekwondo athletes and 9 female Taekwondo junior athletes. The results of the data obtained were compared with the data from previous research as a reference in determining the quality standards of Indonesian Taekwondo junior athletes compared with Taekwondo junior athletes from other countries. Related to anthropometric aspects, the results of this study showed that the body weight, height, and BMI of Taekwondo athletes were in the normal category according to WHO standard. Based on the results of anaerobic capacity measurement, Taekwondo athletes got unfavourable results on an average sprint result of 30 meters. However, the results of vertical jumps and VO2max indicated that Indonesian junior Taekwondo athletes were above the normal category determined previously. This research successfully described the physiological characteristics of Indonesian junior Taekwondo athletes in West Java, East Java, and Central Java student training education centres. The trainers are encouraged to provide a balance concept of aerobic and anaerobic trainings in order to create or foster Taekwondo athletes properly and appropriately.